Tandem application of endophytic fungus Serendipita indica and phosphorus synergistically recuperate arsenic induced stress in rice - Sehar, Shafaque; Feng, Qidong; Adil, Muhammad Faheem; Sahito, Falak Sehar; Ibrahim, Zakir; Baloch, Dost Muhammad; Ullah, Najeeb; Ouyang, Younan; Guo, Yushuang; Shamsi, Imran Haider (Frontiers in Plant Science, 2022)
In the context of eco-sustainable acquisition of food security, arsenic (As) acts as deterrent factor, which easily infiltrates our food chain via plant uptake. Therefore, devising climate-smart strategies becomes exigent for minimizing the imposed risks. Pertinently, Serendipita indica (S. indica), is well-reputed for its post-symbiotic stress alleviatory and phyto-promotive potential. Management of phosphorus (P) is acclaimed for mitigating arsenic toxicity in plants by inhibiting the uptake of the As molecules due to competitive cationic exchange in the rhizosphere. The current study was designed to investigate the tandem effects of S. indica and P in combating As toxicity employing two rice genotypes, i.e., Guodao-6 (GD-6; As sensitive genotype) and Zhongzhe You-1 (ZZY-1; As tolerant genotype). After successful fungal colonization, alone and combined arsenic (10 µM L-1) and phosphorus (50 µM L-1) treatments were applied. Results displayed that the recuperating effects of combined S. indica and P treatment were indeed much profound than their alone treatments, however most of the beneficial influences were harnessed by ZZY-1 in comparison to GD-6. Distinct genotypic differences were observed for antioxidant enzyme activities, which were induced slightly higher in S. indica-colonized ZZY-1 plants, with or without additional P, as compared to GD-6. Ultrastructure images of root and shoot exhibited ravages of As in the form of chloroplasts-, nuclei- and cell wall-damage with enlarged vacuole area, mellowed mostly by combined treatment of S. indica and P in both genotypes. Gene expression of PTHs family transporters were regulated at different levels in almost all treatments across genotypes. Conclusively, the results of this study validated the promising role of S. indica and additional P in mitigating As stress, albeit corroborated that the extent of relevant benefit exploitation is highly genotype-dependent. Verily, unlocking the potential of nature-friendly solutions will mend the anthropogenic damage already been done to our environment.